Spectroscopic characterization of laser-ablated manganese sulfate plasma. (March 2014) - Salik, M.; Hanif, M.; Wang, J.; Zhang, X. Q.
Abstract: In this work, we present the spectroscopic studies of the plasma generated at the surface of manganese sulfate by the fundamental (1064 nm) and second harmonic (532 nm) of a Q-switched Nd:YAG laser. The 4s4p 4 F7/2 → 4s 2 H9/2 at 438.80 nm, 4p 2 I11/2  → 4s 2 2 I11/2 at 440.80 nm, 4p 4 G11/2  → 4s 2 H9/2 at 464.27 nm, 4p 4 F5/2 → 4s 4 D7/2 at 467.16, 4p 4 F5/2  → 4s 2 4 G7/2 at 515.08 nm, and 4p 4 F7/2  → 4s 2 4 G9/2 at 519.65 nm transitions have been used to estimate the electron temperature through the Boltzmann plot method. The number density has been estimated from the Stark broadened profiles of the spectral line 348.30 nm. The spatial behavior of the electron temperature and number density has been examined at different ambient air pressures and with laser irradiance. The temperature and number density are found to be in the range from 9842 K to 9371 K and 1.58 × 10 17 to 3.26 × 10 16 cm −3 for the 1064 nm laser, from 9668 to 9297 K and 2.27 × 10 17 to 5.79 × 10 16 cm −3 for the 532 nm laser.